TURNING RIVERS INTO LIVING LABORATORIES: ACTION-BASED EDUCATIONAL TOURISM TO ENHANCE YOUTH ECOLOGICAL STEWARDSHIP - Delamontano, Eldo; Endyana, Cipta; Winoto, Yunus; Novianti, Evi (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
This study examines the influence of action-based educational tourism on bridging the "knowledge-action gap" within environmental education. The research aims to evaluate how motivation, awareness, knowledge, and active participation through the "SatuBumi River Cleanup" program shape the pro-environmental behavior (PEB) of high school and university students. Using a quantitative-explanatory method with Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 206 respondents via purposive sampling. The results reveal that environmental motivation (beta = 0.403) and active participation (beta = 0.279) are the primary drivers of sustainable behavioral change, while environmental knowledge showed no statistical significance (beta = 0.021). The novelty of this research lies in the integration of Richards’ 3S storytelling framework with physical waste mitigation, transforming polluted river ecosystems into "living laboratories" for socio-ecological transformation. This study challenges the traditional information-delivery paradigm by demonstrating that emotional resonance and physical agency are more effective than theoretical instruction. The implication for educational science suggests a shift toward experiential, narrative-driven pedagogy to foster genuine ecological stewardship. By providing empirical evidence of how immersive environments catalyze behavioral shifts, this research contributes to the broader development of science in educational methodology, advocating for the institutionalization of action-based learning to achieve long-term sustainability goals.